Frequent Errors in Consonant Sound Production of Elementary Education Teachers at Visayas State University - Precious C Domingo (E-Structural (English Studies on Translation, Culture, Literature, and Linguistics), 2020)
Abstract. Pronunciation is essential in language learning; thus, English learners as a second language should strive for articulateness in sound patterns in English. This study aimed to determine the commonly mispronounced consonant sound of the Bachelor of Elementary Education students of the Visayas State University according to the manner and place of articulation. The instrument used in the study is the Golden-Fristoe Test of Articulation, which is composed of 44 words containing the different consonant sounds in English. The study results revealed that most consonant sounds misarticulated by the respondents were fricatives /z/, the nasal consonant sound /m/, the fricative sound /ð/, the affricate /dz/. With respect to the place of articulation, most consonant sounds misarticulated by the respondents concerning the place of articulation were alveolar /z/, the velar consonant sound /m/, the interdental sound /ð/, the post-alveolar /dz/. With these results, it is expected for the Filipino English language teachers to focus on teaching the alveolar and labiodental fricatives in teaching the consonant sounds because most students failed to articulate these sounds correctly.Keywords: English language, consonant sounds, pronunciationAbstrak.  Pelafalan sangat penting dalam pembelajaran bahasa. Oleh karena itu, pelajar bahasa Inggris sebagai bahasa kedua harus berusaha keras untuk mengartikulasikan pola bunyi dalam bahasa Inggris. Penelitian ini bertujuan untuk mengetahui bunyi konsonan yang sering salah diucapkan pada mahasiswa S1 Pendidikan Dasar Universitas Negeri Visayas menurut cara dan tempat artikulasi. Instrumen yang digunakan dalam penelitian ini adalah Golden-Fristoe Test of Articulation, yang terdiri atas 44 kata yang berisi bunyi konsonan yang berbeda dalam bahasa Inggris. Hasil penelitian menunjukkan bahwa bunyi konsonan yang paling banyak salah artikulasi oleh responden adalah bunyi konsonan / z /, bunyi konsonan nasal / m /, bunyi frikatif / ð /, afrikat / dz /. Sehubungan dengan tempat artikulasi, sebagian besar bunyi konsonan yang salah diartikulasikan oleh responden mengenai tempat artikulasi adalah alveolar / z /, bunyi konsonan velar / m /, bunyi interdental / ð /, post-alveolar / dz /. Dengan hasil tersebut diharapkan para pengajar bahasa Inggris Filipina dapat fokus dalam mengajarkan frikatif alveolar dan labiodental dalam mengajarkan bunyi konsonan karena sebagian besar siswa gagal mengucapkan bunyi tersebut dengan benar. Kata kunci: bahasa Inggris, bunyi konsonan, pelafalan